(untitled) (International Journal of Current Engineering and Technology, 2015)
The purpose of this paper is to further the knowledge of pigging and scraper trap in terms ofFEM as a powerful tool. Where reaction forces and expected displacements have been investigated, consequently a new particular design has been suggested for a pig in scraper trap system, thereafter some concluded points have been illustrated clearly